Certain dietary patterns including potatoes are associated with higher and lower diet quality and physiological measures in children and adults, NHANES 2001-2018 - Fulgoni, Kristin; Fulgoni, Victor L. (Frontiers in Nutrition, 2022)
A large percentage of daily vegetable intake is attributed to white potatoes, but limited information is available on how potatoes are incorporated into dietary patterns in the US. Therefore, the objective of this study was to determine food patterns that include potatoes and to compare the associated diet quality and association with biomarkers to a food pattern without potatoes. Data from subjects 2-18 and 19+ years and older who participated in the What We Eat in America portion of the National Health and Nutrition Examination Survey cycles 2001-2018 were utilized in the current study. Diet quality was assessed using the Healthy Eating Index-2015. Multiple food clusters containing potatoes were identified with several having higher and lower diet quality as compared to a food pattern without potatoes. Differences in biomarkers were also observed between subjects consuming potato and non-potato patterns, with differences in anthropometric variables in both groups and total- and HDL-cholesterol and insulin levels in adults. The percentage of calories from potatoes across patterns was small, ~9-12%, suggesting the differences observed in diet quality and biomarkers were due to other food categories consumed in the pattern. This study suggests potatoes can be incorporated as part of a healthy eating pattern.